The Importance of Financial Reporting Assistance for Persis Banjaran Jam'iyyah Businessmen - Lestari, Rini; Suangga, Asri; Nurcholisah, Kania; Nurjaya, Dimas; Rahmat Ramdani, Boyke; ., Nurfahmiyati; Nur Azizah, Asyifa; Handoyono, Widjaya (KnE Social Sciences, 2023)
Training and mentoring are carried out for businessmen Jam’iyyah (Persis Banjaran) Bandung district. Financial management, through financial recording and reporting, is one of the main problems faced by these businessmen, which is still done minimally. This is due to the lack of knowledge about the importance of financial reporting in optimizing businesses decision-making and improving financial performance. Appropriate training and mentoring can be a solution to the problems faced by businessmen Jam’iyyah (Persis Banjaran). This activity is carried out offline in the form of face-to-face training for 2 meetings while still paying attention to health protocols on Saturday, November 13, 2021 and March 26, 2022. After training and offline assistance, our team provided time for participants to consult online through social media. Based on discussions held with businessmen and the head of the social and economic field of PC Persis Banjara (as partners), this partnership can be continued with programs that reach the wider community. This training and assistance is expected to raise the enthusiasm and consistency of businessmen in carrying out financial recording and reporting in the simplest way, but still being accountable. Keywords: businessmen, financial reporting, business decisions